Erratum to: Contributions of the anterolateral complex and the anterolateral ligament to rotatory knee stability in the setting of ACL Injury: a roundtable discussion (Knee Surgery, Sports Traumatology, Arthroscopy, (2017), 25, 4, (997-1008), 10.1007/s00167-017-4436-7) - Williams,A; Amis,A; Zaffagnini,S; Karlsson,J (Knee Surgery, Sports Traumatology, Arthroscopy, 2018)
© 2016, European Society of Sports Traumatology, Knee Surgery, Arthroscopy (ESSKA). In the original article, one of the co-authors’ name has been published incorrectly. The correct name should be Jeremy M. Burnham. The original article has been updated accordingly.